Change Management in the Implementation of the Independent Curriculum in Sekadau District Secondary Schools - Vinawuli Tabais, Yesi; Novianti, Iluminata; Emakulata, Maria; Radiana, Usman (CV. Pusdikra Mitra Jaya, 2024)
The implementation of the Merdeka Curriculum in secondary schools in Sekadau Regency, represents advancement in addressing globalization and technological progress, with the objective of fostering a more flexible, student-centered education that enhances student competency and engagement. This study seeks to examine change management during the introduction of the Independent Curriculum in secondary schools within Sekadau Regency. This study employs qualitative methodologies, using data gathering via semi-structured interviews and direct observation. Interviews were performed with school principals, educators, and administrative personnel to understand the problems and tactics employed in the curriculum modification process. Field observations were conducted to assess the implementation of the curriculum in classroom activities. The findings identify five principal barriers: the necessity for teacher retraining, technological and infrastructure constraints, cultural resistance, teacher fatigue during the shift, and insufficient training. This study underscores the significance of ongoing training, enhancement of technology infrastructure, and systematic change management within context. Proactive support from government and educational leadership is crucial for the effective implementation of the Independent Curriculum and the enhancement of educational quality in Sekadau Regency.